Synopsis of Amphipoda from two recent Ross Sea voyages with description of a new species of Epimeria (Epimeriidae, Amphipoda, Crustacea) - Lörz, Anne-Nina (Zootaxa, 2009)
Two recent voyages to the Ross Sea in 2004 and 2008 collected over 3000 benthic Amphipoda. The composition of 30 amphipod families is presented, and a focus is given to the family Epimeriidae from which a new species described. Epimeria larsi sp. nov. from 1950 m depth, is the deepest occurring species of the genus known from Antarctic waters. This increases the number of known species of Epimeriidae from Antarctica to 27. Epimeria larsi can be distinguished from similar species by the unique combination of following characters: coxa 5 posteroventral corner produced, epimeral plate posteroventral corner rounded, and coxa 1–3 apically rounded.